Edukasi Keamanan Data dan Privasi di Era Kecerdasan Buatan melalui Literasi Digital Sekolah Dasar - Yuniar Andi Astuti; Ester Hervina Sihombing; Sujarwo Sujarwo; Sondang Sondang; Berupilihen Br Ginting; Mega Puspita Sari (Jurnal IPTEK Bagi Masyarakat, 2026)
The development of artificial intelligence (AI) technology has brought significant changes to various aspects of life. However, it has also given rise to serious challenges related to data security and user privacy protection. The low level of digital literacy among the public, particularly in understanding the risks of data breaches and the misuse of personal information, has increased vulnerability to cybercrime in the digital era. This community service activity aims to enhance public knowledge, awareness, and skills in safeguarding data security and privacy amid the rapid adoption of AI-based technologies. The activity was implemented using an educational and participatory approach through workshops, interactive lectures, discussions, case simulations, and hands-on practice in securing digital accounts. The program involved 20 participants consisting of teachers and staff at SD Negeri 060922 Medan. Evaluation was conducted through pre-tests and post-tests to measure improvements in participants’ understanding. The results indicate an average increase in participants’ knowledge of 40%, along with heightened awareness of the importance of password management, privacy settings, and vigilance against cyber threats. This activity demonstrates that community-based education on data security and privacy is effective in improving digital literacy and fostering safer and more responsible technology use behaviors. Therefore, similar initiatives should be carried out on a sustained basis to support the development of a secure, ethical, and adaptive digital ecosystem in response to advancements in artificial intelligence.